2016
DOI: 10.1063/1.4948947
|View full text |Cite
|
Sign up to set email alerts
|

Reduced defect density at the CZTSSe/CdS interface by atomic layer deposition of Al2O3

Abstract: The greatest challenge for improving the power conversion efficiency of Cu2ZnSn(S,Se)4 (CZTSSe)/CdS/ZnO thin film solar cells is increasing the open circuit voltage (VOC). Probable leading causes of the VOC deficit in state-of-the-art CZTSSe devices have been identified as bulk recombination, band tails, and the intertwined effects of CZTSSe/CdS band offset, interface defects, and interface recombination. In this work, we demonstrate the modification of the CZTSSe absorber/CdS buffer interface following the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 42 publications
0
49
1
1
Order By: Relevance
“…We note that a couple of papers on passivation of top CZTSe surfaces with a thin Al 2 O 3 layer were very recently published while we were preparing this manuscript . Our work differs from those studies in that we have demonstrated that the chemical role of the Al 2 O 3 passivation layer, that is the suppression of Cu–Cd inter‐diffusion leading to a cleaner CZTSe/CdS junction, is responsible for the improved V oc .…”
Section: Resultsmentioning
confidence: 63%
“…We note that a couple of papers on passivation of top CZTSe surfaces with a thin Al 2 O 3 layer were very recently published while we were preparing this manuscript . Our work differs from those studies in that we have demonstrated that the chemical role of the Al 2 O 3 passivation layer, that is the suppression of Cu–Cd inter‐diffusion leading to a cleaner CZTSe/CdS junction, is responsible for the improved V oc .…”
Section: Resultsmentioning
confidence: 63%
“…Erkan et al also used an ALD-coated Al 2 O 3 layer between a CZTSSe absorber layer and CdS layer. It was shown statistically that the passivated solar cells have higher V OC , almost similar J SC and lower FF as compared to the unpassivated solar cells [15]. However, in general the passivated and unpassivated CZTSSe solar cells in their study had lower performance than the state of the art especially due to low FF.…”
Section: Introductionmentioning
confidence: 79%
“…Recently, several studies focused on passivation of the p-n junction in kesterite solar cells by introducing n-type metal oxide layers such as Al 2 O 3 [15], [16] or TiO 2 [17] layers between the kesterite absorber and CdS buffer layers which did improve V OC . The improvement of V OC using the passivation layers can be explained by reducing the interface recombination by chemical passivation (reduction of interface trap density) and field effect passivation (formation of a fixed charge density and consequently decreasing the charge carrier concentration at the interface).…”
Section: Introductionmentioning
confidence: 99%
“…These encouraging findings suggest that low-cost and environmentally friendly CBD Zn(O, S) films promise to be used as the Cd-free buffer layer for solar cells with kesterite thin film [36]. Table 2 below summarize optical band alignment of different buffer/absorber interfaces below: CdS are widely used as a buffer layer in CZTS-based solar cells [37]. However, the carrier recombination at the interface between CZTS absorber and Cds buffer results in a decrease of Voc.…”
Section: Effect Of the Buffer Layer In Device Architecturementioning
confidence: 97%